Pengaruh Pembelajaran Matematika Terintegrasi Islam Terhadap Pembentukan Karakter Siswa - Nada Aviola; Shyfatul Hayati; Windi Pebria; Annisa Annisa; M. Imamuddin (KOLONI, 2023)
Mathematics is one of the sciences that has an important role in education. Mathematics education also contains character values in it. Among the character values are discipline, honesty, hard work, creativity, curiosity, independence, communicative and responsibility. So that by learning mathematics can also form the character of students. So in this paper the author conducted a study on “the influence of Islamic integrated mathematics learning on the formation of Student character". The research methodology used is literature review or literature review. In this paper, the team of authors describes some of the results of the literature review, namely: 1) the trend of student character formation through mathematics learning and Islamic integrated mathematics learning every year, 2) the subject of student character formation research through mathematics learning and Islamic integrated mathematics learning, 3) the research methods used in the Journal of student character formation through mathematics, 4) the character formed through the learning of mathematics and mathematics learning integrated islam. Based on the results of the literature study, it was found that mathematics learning and Islamic integrated mathematics learning have a good influence on the formation of student character can be seen from the formation of honest, fair, responsible, consistent, confident and conscientious attitudes that exist in students. Keywords : Influence, Learning Mathematics, Integrated Islam, Character Building